PEMBELAJARAN BAHASA ARAB DARING BERBASIS STRATEGI KARRONA DI MASA PANDEMI COVID-19 - Maria Ulfah Syarif (Didaktika : Jurnal Kependidikan, 2020)
One of the obstacles in the implementation of online learning during Covid-19 pandemic is the lack of lecturers and students’s readiness in mastering e-learning support applications. In addition, the large amount of assignments precisely can trigger students’ psychosocial stresses that may diminsih the online learning effectiveness. The lecturers, therefore, are required to be more creative to make an interesting learning, including in Arabic learning.  Karrona, an innovative learning strategy, is a song media-based method focusing on strengthening the understanding of qawāid substance that is applied to overcome the ineffectiveness of online learning Arabic. This study then aims to investigate how the effectiveness of Karrona strategy to increase qawāid understanding and to improve vocabulary mastery in online Arabic learning during pandemic covid-19. This research employed a mixed method design, involving the mixing of both quantitative and qualitative approach. This study involved 176 students of IAIN Bone as well as used observation and questionnaires techniques to collect the data. The major findings of this study show that the Karrona strategy is briefly effective in increasing student interest and motivation to learn Arabic. Moreever, this strategy can improve students’ qawāid understanding and mufradāt mastery.